2015
DOI: 10.1515/sgem-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of Blast Loads from Near-Field Ground Explosions in Air

Abstract: Numerical simulations of air blast loading in the near-field acting on the ground have been performed. A simplified blast model based on empirical blast loading data representing spherical and hemispherical explosive shapes has been simulated. Conwep is an implementation of the empirical blast models presented by Kingery and Bulmash, which is also implemented in the commercial code LS-DYNA based on work done by Rahnders-Pehrson and Bannister. This makes it possible to simulate blast loads acting on structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The TNT explosives utilize the high explosive combustion material model keyword *MAT_HIGH_EXPLOSIVE_BURN within the LS‐DYNA material library, combined with the EOS_ JWL state function equation. References Hallquist 34 and Dobrociński and Flis 35 are used to define the explosive material parameters. The air is simulated using the *MAT_NULL keyword model, combined with a linear polynomial state function 34 .…”
Section: Numerical Simulation Analysismentioning
confidence: 99%
“…The TNT explosives utilize the high explosive combustion material model keyword *MAT_HIGH_EXPLOSIVE_BURN within the LS‐DYNA material library, combined with the EOS_ JWL state function equation. References Hallquist 34 and Dobrociński and Flis 35 are used to define the explosive material parameters. The air is simulated using the *MAT_NULL keyword model, combined with a linear polynomial state function 34 .…”
Section: Numerical Simulation Analysismentioning
confidence: 99%
“…Three models were created for the studied RC column SEIS-8 with different erosion values 0.025, 0.05 and 0.10, using the mesh sizing 15×15×18.75 mm. The flow stress is assigned using Von Mises stress as expressed by Johnson-Cook (J-C) [46]. Figure 16 shows the failure mode shapes corresponding to the three erosion values; the maximum displacement values are plotted in Figure 17 compared to the experimental value.…”
Section: Effect Of Erosion Valuesmentioning
confidence: 99%
“…It was concluded that the coupled MM-ALE method is useful in cases where the scaled distance is above 0.4, the problems that may arise from large air elements can be compensated by increasing the air density up to a certain rate, and larger air elements can be used in simulations where the scaled distance is relatively large (Han and Liu, 2015). Flis and Dobrociński, simulated hemispherical detonation waves on 1 kg of TNT detonated on a 1m x 1m steel plate on the ground plane with the numerical methods CONWEP, MM-ALE and SPH and concluded that the MMALE method is the only method that gives approximate results in contact explosions (Flis and Dobrociński, 2015). They observed that the CONWEP method could not generate detonation waves in the correct form in explosions that were closer than three times the charge radius and when the scaled distance was about 1 𝑚 𝑘𝑔 3 1 ⁄…”
Section: Introductionmentioning
confidence: 99%